UPAYA DALAM PENGEMBANGAN PENDIDIKAN KARAKTER PADA KURIKULUM 2013 DI KELAS V SEKOLAH DASAR - Eni Marta; Rinja Efendi (STKIP ROKANIA, 2019)
This study aims to find out character education in the 2013 curriculum and the curriculum and to find out the efforts made in developing character education in learning in elementary schools. This research was carried out in 003 Public Elementary Schools in the VA and VB Classes. The technique of collecting data in this study uses observation, interviews and documentation. Data analysis techniques using descriptive qualitative data analysis techniques. The results of the study based on observations and interviews showed that in the development of character education in elementary school 003 Rambah is still not optimally implemented, this can be seen from the learning tools used by teachers such as syllabus that does not contain character education and lesson plans that contain character education even though development needs to be done. While students in the learning process have shown attitudes or characters such as religious, disciplined and responsible. It can be concluded that character education at elementary school 003 Rambah is relatively good and needs development in its implementation.